Association of KMT2C/D loss‐of‐function variants with response to immune checkpoint blockades in colorectal cancer. Issue 4 (24th January 2023) - Liu, Ruiqi; Niu, Yanling; Liu, Chao; Zhang, Xin; Zhang, Jinku; Shi, Min; Zou, Wenbo; Gu, Binbin; Zhu, Honglin; Wang, Danhua; Yuan, Hongling; Li, Wei; et al.
Abstract: Immune checkpoint inhibitors (ICIs) have become important treatment strategies, yet responses vary among patients and predictive biomarkers are urgently needed. Mutations in KMT2C and KMT2D lead to increased levels of genomic instability. Therefore, we aimed to examine whether KMT2C/D mutations might be a predictor of immunotherapeutic efficacy. Here, we investigated the associations of KMT2C/D loss‐of‐function (LOF) variants with tumor mutation burden (TMB), MSI‐H, PD‐L1 expression, the levels of tumor‐infiltrating leukocytes (TILs), and clinical response to ICIs. It was found that KMT2C/D LOF variants were associated with higher TMB. Compared with the non‐LOF group, the proportion of patients with MSI‐H tumors was larger in the LOF group. PD‐L1 expression was higher in the LOF group only for colorectal cancer in both the Chinese and The Cancer Genome Atlas cohorts. Importantly, KMT2C/D LOF variants were associated with decreased regulatory T cells and increased levels of CD8 + T cells, activated NK cells, M1 macrophages, and M2 macrophages in colorectal cancer. However, there was no significant association between KMT2C/D LOF and TILs levels in other cancer types. Consistently, the results showed that KMT2C/D LOF variants were associated with prolonged overall survival only in colorectal cancer ( p  = 0.0485). We also presented that patients with KMT2C/D LOF mutations exhibited a better clinical response to anti‐PD‐1 therapy in a Chinese colorectal cancer cohort ( p  = 0.002). Taken together, these results suggested that KMT2C/D LOF variants could be a useful predictor for ICIs efficacy in colorectal cancer. In addition, the predictive value of KMT2C/D LOF variants was consistent with their association with TILs levels.